Anti Perkinsus olseni Monoclonal Antibody Generation Using Hypnospores as Antigens - Kaewsalabnil, Sirirat; Buewkeaw, Anumart; Watanachote, Janjarus; Leethochavalit, Supannee; Khongchareonporn, Nanthika (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Antibodies are valuable for the detection, identification, and diagnosis of pathogens in many fields, including aquaculture. In this study, we aimed to produce monoclonal antibodies (mAbs) against the parasite Perkinsus olseni, isolated from the clam Paphia undulata in Thailand. The mAbs were characterized using dot blotting and immunohistochemistry techniques in order to identify their class and their ability to detect the hypnospores and zoospores of P. olseni. Immunoreactions between the obtained mAbs and P. olseni produced black or grey spots according to the concentration of parasites detected by the mAbs. The quantitative detection thresholds of hypnospores for the two most strongly reactive mAbs were 105 cells/mL (producing grey spots) to 107 cells/mL (producing black spots), and more than 107 cells/mL (grey spots) for zoospores. Both mAbs showed immunoreactivity at the surface of trophozoite cells of P. olseni in infected clam tissues as assessed by immunohistochemistry analysis, indicating that they could be used for the detection and identification of P. olseni infection in commercial Pa. undulata production.